Performance of Groundwater Irrigation System as Perceived by Farmers in West Bengal - Subhajit Mukherjee, Arijit Roy; Souvik Ghosh (Indian Journal of Extension Education, 2022)
In spite of being the most fundamental stakeholder, farmers often receive the least attention in the assessment of irrigation performance. The study assessed the performance of groundwater irrigation systems being managed by water user associations (WUAs) in the Burdwan (East) district of West Bengal from the perspectives of farmers during the year 2019. A random sample of 120 farmers under four groundwater irrigation systems perceived that most of the parameters of irrigation performance in terms of irrigation service utility at a higher level with a mean perception score >4.0 except for the certainty of water delivery (2.67) leading to overall mean perception score 4.12 in Kharif season. Farmers perceived similarly in rabi season with an overall mean perception score of 4.15; however, the overall perception of farmers regarding irrigation in the summer season was relatively low (3.78). Overall irrigation performances under the jurisdiction of WUAs were perceived very good by all the farmers for all three seasons with index values of more than 93 percent. The farmers’ participation in irrigation management has helped in better water management that advocates for promoting participatory irrigation management through WUAs in all the minor irrigation systems to overcome low irrigation efficiency and other management constraints being faced in irrigated areas.